Pilot Society and the Energy Transition - Ryghaug, Marianne; Skjølsvold, Tomas Moe (Springer Nature, 2021)
This open access book examines the role of pilot and demonstration projects as crucial devices for conducting innovation in the context of the energy transition. Bridging literature from sustainability transitions and Science and Technology Studies (STS), it argues that such projects play a crucial role, not only in shaping future energy and mobility systems, but in transforming societies more broadly. Pilot projects constitute socio-technical configurations where imagined future realities are materialized. With this as a backdrop, the book explores pilot projects as political entities, focusing on questions of how they gain their legitimacy, which resources are mobilized in their production, and how they can serve as sites of public participation and the production of energy citizenship. The book argues that such projects too often have a narrow technology focus, and that this is a missed opportunity. The book concludes by critically discussing the potential roles of research and innovation policy in transforming how such projects are configured and conducted.